A Zymography Analysis of Protease Activity Present in Commercial Fibrinolytic-Lumbrokinase Agents in Indonesia - Kartika, Ronald; Santoso, Adit W.; Timotius, Kris H. (Jour Med Resh and Health Sci, 2024)
Background: Fibrinolytic agents are useful in eliminating blood clotting in several disorders. Beside Nattokinase, Lumbrokinase is often used the main ingredient of fibrinolytic agent commercially. The objectives of this study were to inventory and categorise fibrinolytic agents available commercially based on the kind of their bioactive compound (fibrinolytic enzyme), and to do Zymography analysis to compare the proteolytic activity of several Lumbrokinase containing agents. Method: Fibrinolytic agents available commercially were collected from the drug store in Jakarta. They were classified based on the information available in the leaflet or in the drug box. The Casein-Proteolytic Zymograph was carried out for the Lumbrokinase containing agents. Result: The fibrinolytic agents in commercially could be categorised into two types, Lumbrokinase and Nattokinase containing enzymes. Zymography analysis showed that Lumbrokinase-fibrinolytic agents have different strength. Their PAGE profile showed that several bands were missing. Conclusion: Two fibrinolytic enzymes are used for main ingredient, Lumbrokinase and Nattokinase. Fibrinolytic agents with Lumbrokinase are different in their strength and their protein profile is not exactly similar.